Design of Porang Cultivation Development System Model in Madiun Regency: Desain Model Sistem Pengembangan Budidaya Porang di Kabupaten Madiun - Ajun Wahyu Pamungkas; Akbar Hardianysah; Ma'ruf Pambudi Nurwantara (Universitas Merdeka Madiun, 2024)
Porang is a tuber plant with extensive benefits, so it has the potential to be developed. However, this potential is accompanied by many existing problems. Identification to overcome it. A system approach to overcome it. This study aimed to design a porang cultivation development system model in Madiun Regency. The research method uses primary data and secondary data. They start with identifying the porang cultivation process, identifying needs analysis, and using case diagrams. The study results showed that acceptable inputs consisted of planting good quality seeds and clearing the land to make it easier in the planting stage. Unacceptable inputs consisted of planting porang seeds of poor quality and planting on less sump needed to be more. Stakeholders consisted of farmers and farmer groups—resources comprised of land, seeds, fertilizers, capital, and agricultural tools. The roles arranged were to increase porang productivity, make porang a superior commodity, and open up business opportunities. Threats consisted of expensive porang seeds, scarcity of fertilizers, and shortages of workers. Controls consisted of giving fertilizer on a specified scale, planting according to SOP, and monitoring the land. Acceptable output is producing good porang plants, attracting other farmers to cultivate porang plants, and increasing the selling value of porang. Unacceptable output is poor porang harvest quality/crop failure, not attracting farmers to imitate porang cultivation, and low porang selling price. Based on the results of this study, it is concluded that the porang plant cultivation process is expected to produce good porang plants, attract other farmers to cultivate porang plants, and increase the selling value of porang.